Assessing agricultural practices and insecticides resistance for effective malaria vector control in northwestern Iran - Madineh Abbasi; Saideh Yousefi; Fatemeh Nikpour (Tropical Medicine and Health)
Abstract Background After three years with no local transmission of malaria, an outbreak occurred in Iran in 2022. Key malaria control methods in Iran are including indoor residual spraying (IRS), long-lasting insecticide-treated nets (LLINs), and prompt diagnosis and treatment of malaria cases. Anopheles sacharovi is one of the main malaria vectors in Iran. This study aimed to determine the insecticides resistance status of An. sacharovi in northwestern Iran, to inform effective vector control programs in this region. Methods Larval stages of An. sacharovi were collected from various larval habitats located in the villages along the Aras River. Adult susceptibility tests were performed on An. sacharovi using diagnostic doses of insecticides accordance to World Health Organization (WHO) guidelines. The study also evaluated agricultural insecticide and fertilizer usage alongside the presence of natural mosquito predators in breeding sites in the study area. Results Alongside various chemicals such as silica, humic acid, superphosphate, sulfur, urea, and solupotasse at different dose levels, organophosphorus and pyrethroid insecticides are commonly used in rice fields and orchards. Anopheles sacharovi displayed diverse reactions to insecticides, demonstrating resistance to DDT but sensitivity to malathion, and showing similar reactions to carbamate and pyrethroid insecticides. Conclusions These results provide significant insights into agricultural practices and the presence of mosquito larvae in the study area. The extensive use of a specific herbicide illustrates its popularity among farmers for weed control, while other agricultural products focus on enhancing soil fertility and productivity. The absence of mosquito larvae in habitats with predators indicates the usefulness of these predators in controlling the population of mosquitoes. The resistance of mosquitoes to certain insecticides highlights the need for careful selection and intermittent use of insecticides in vector control programs. These findings can inform the development of targeted strategies to reduce malaria transmission risks. Further research is essential for assessing the effectiveness of these interventions.